Principles of Evaluating Roentgen Diagnostic Classifications - Koivisto, Erkki (Methods of Information in Medicine, 1969)
The utilization of computers has made the classification of roentgen diagnostic findings more important than ever. In the present paper principles of evaluating roentgen diagnostic classifications are considered on the basis of practical experience. In the appraisal of roentgen diagnostic classifications the following characteristics are considered essential:1.) relative number of specific findings in a clinical collection;2.) retrieval capability;3.) percentage of specified diagnoses in relation to the total number of diagnoses contained in the classification system.